PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI VARIABEL INTERVENING PADA KANTOR UNIT PENYELENGGARA BANDAR UDARA INANWATAN-SORONG SELATAN - Madhuri Madhuri; Herningsih Herningsih; Amiruddin Matutu (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This research deals with employee performance which is an important element in organizational goals. This study aims to analyze the effect of competence and motivation on employee performance by using information technology as an intervention variable at the Inanwatan Airport Office Unit, South Sorong Regency. This research is descriptive quantitative research. The sample used in this study found 32 respondents. The sample selection used the saturated sampling method. The data analysis method uses Partial Least Square (PLS) using smartPLS software version 3.3.5. The results showed that competence and motivation had a significant effect on employee performance. Competence and motivation are also known to have a significant effect on the use of information technology. Furthermore, the use of technology has a positive effect on employee performance. Explicitly the use of information technology acts as a mediation between motivation and employee performance, does not mediate the influence between competence and employee performance.